Against the Odds - Ignatow, Amy (Amulet Books, 2018)
The Odds are still trying to cope with their strange powers that keep evolving. Now Martina can see the invisible and Nick can sometimes move a lot farther than four inches. With the help of some Amish teens and Ed, the invisible bus driver, the kids will unearth an evil experiment in which they are the test subjects.